Electrical engineering learn it, try it! - Sobey, Edwin J. C. 1948- (North Mankato, Minnesota Capstone Press, a Capstone imprint, 2018)
An introduction to careers in electrical engineering and includes projects for practicing related skills.
"Dabble lab."
Includes bibliographical references (page 47) and index.
Keywords: Electrical engineering -- Juvenile literature; Electrical engineering; Electrical engineering